On congestion control strategy for space delay/disruption tolerant networks - cheng YANHong; jun ZHANGQing; Yong SUN (Tongxin xuebao)
To address the congestion control problem in space DTN(delay/disruption tolerant networks), an EOCC(early offloading-based congestion control) strategy was proposed. As space DTN was often subject to high latency and end-to-end continuous connectivity could not be guaranteed, EOCC takes measures before congestion occurs with local information only. More specifically, EOCC will monitor the buffer rate at all times and attempts to relieve the storage pressure by early offloading the node buffer through non-best paths which are earlier than the best path when the network is about to congest. Simulation results show that contact graph routing with the proposed congestion control strategy achieves better performance.